KONSUMSI PUDING BAHIRAT (BAHAM HIJAU, MERAH DAN BIT) TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA IBU HAMIL - Febriana Rosi (Yayasan Pendidikan Medika Indonesia, 2023)
Anemia in pregnancy is caused by physiological changes, metabolism and an increase in plasma volume by 30-50% which causes red blood cells to decrease so that pregnant women are prone to anemia and inadequate intake of iron. Anemia can have an impact on bleeding during childbirth, stunted fetal growth, premature birth, low birth weight and even anemia is a cause of death in the mother and fetus. The need for iron in the second trimester is 35 mg/day and in the third trimester it is 39 mg/day. Iron during pregnancy can be met by consuming green spinach, red spinach and beets. The iron content in green spinach is 3.9 mg/100g, red spinach is 7mg/100g and beets is 7.4mg/100g. The combination of these three ingredients has never been studied before, which is processed into pudding to make it attractive and disguise the taste of the three ingredients. The aim of the study was to determine the effect of consumption of bahirat pudding (green, red and beetroot spinach) on increasing hemoglobin levels in pregnant women. The research method uses a quasi-experimental design with a pre-test and post-test control group design. The number of samples were 44 pregnant women in the second and third trimesters who experienced anemia, 22 pregnant women in the intervention group were given bahirat pudding for 10 days while the control group was given regular pudding without bahirat for 10 days. The data were analyzed using the Wilcoxon test to obtain an average hemoglobin level in the group. the intervention was -4.05 <0.05, while the control group was -0.427 <0.05 so that H0 was rejected and there was an effect of consumption of bahirat pudding on increasing hemoglobin levels of pregnant women.